Plantio direto de pimentão sobre diferentes resíduos vegetais - SOUSA, Augusto Silva; VENDRUSCOLO, Eduardo Pradi; SERON, Cássio de Castro; MARTINS, Murilo Battistuzzi; POLO, Gabriel Furlan (ANAIS DO ENIC, 2022)
-